Managerial and Scale Efficiency of Hybrid Corn Farming: A Data Envelopment Analysis (DEA) Approach: Efisiensi Manajerial dan Skala Usaha Jagung Hibrida: Analisis dengan Data Envelopment Analysis (DEA) - Putri Liani; Andi Nuddin; Andi Sitti Halimah; Abdul Aziz Ambar (Jurnal Ilmiah Sosio Agribis, 2026)
This study analyzes the managerial and scale efficiency levels of hybrid corn farms in Luyo District, Polewali Mandar Regency, to formulate production performance improvement strategies. Applying an output-oriented Data Envelopment Analysis (DEA) approach, the research evaluates 101 farmers designated as Decision Making Units (DMUs). The analysis decomposes technical efficiency into Pure Technical Efficiency (PTE) to assess managerial capacity and Scale Efficiency (SE) to determine production scale appropriateness. Findings reveal an average technical efficiency (TE) of 0.686, implying a potential production increase of 31.4% without additional inputs. Average managerial efficiency (PTE) reached 0.821, reflecting that farmers' pure technical capacity in managing inputs is relatively high. However, the average scale efficiency (SE) was 0.833, with 95% of farmers operating under Increasing Returns to Scale (IRS). This suggests that most farms still operate on a small scale, where additional inputs can significantly boost output. The study also identifies three DMUs as best-practice benchmarks. It is concluded that farm inefficiency in the study area is primarily driven by inappropriate production scale rather than managerial deficits. Consequently, efficiency improvement strategies should focus on scale development and the rationalization of input allocation.